Plant meiosis: the means to 1N. - Bhatt, A; Canales, C; Dickinson, H (2001)
Meiosis is pivotal in the life history of plants. In addition to providing an opportunity for genetic reassortment, it marks the transition from diploid sporophyte to haploid gametophyte. Recent molecular data suggest that, like animals, plants possess a common set of genes (also conserved in eukaryotic microorganisms) responsible for meiotic recombination and chromosome segregation. However, unlike animals, plant meiocytes do not differentiate from a pool of primordial germ cells, but rather arise de novo from a germline formed from sub-epidermal cells in the anthers and ovules. Mutants defective in the specification of these reproductive cell lines and disrupted in different aspects of the meiotic process are beginning to reveal many features unique to plant meiosis.